Study on Risk Assessment Methods for Geological Storage of Carbon Dioxide - Zhang, Zidie; Zhang, Xuegu; Niu, Yechao; Li, Xia; Yang, Fu; Yue, Yujing; Li, Shi (International Journal of Natural Resources and Environmental Studies, 2025)
Carbon dioxide capture and storage (CCS) represents an effective approach for mitigating CO₂ emissions. However, the potential leakage of stored CO₂ poses significant risks to both the surrounding environment and human health, necessitating comprehensive risk assessment and management of CCS systems. This paper reviews the fundamental principles and applications of commonly employed methods for the risk assessment of CO₂ geological storage and provides insights into future development trends.